Economic evaluation of margetuximab vs. trastuzumab for pretreated ERBB2-positive advanced breast cancer in the US and China - Tang, Zhiyuan; Xu, Xin; Gao, Jie; Chen, Ling; Zhu, Qiuyan; Wang, Jinli; Yan, Xiaoyu; Chen, Bohua; Zhu, Yumei (Frontiers in Public Health, 2022)
Abstract: Compared to trastuzumab plus chemotherapy, margetuximab plus chemotherapy has exhibited proven clinical benefits in patients with pretreated ERBB2-positive advanced breast cancer. However, the cost-effectiveness of this new regimen remains to be investigated. Objective: To assess the economic evaluation of margetuximab plus chemotherapy over trastuzumab plus chemotherapy for women with pretreated ERBB2-positive advanced breast cancer in the United States (US) and China. Methods: Based on the SOPHIA trial, a three-state Markov model was developed to compare the cost and efficacy of margetuximab to trastuzumab for previously treated women with ERBB2-positive advanced breast cancer. The model inputs were derived from existing literature and the US life table. Primary outcomes included lifetime costs in US dollars, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER). Deterministic and probabilistic sensitivity analyses were conducted to evaluate the impact of uncertainty. Results: The base case analyses demonstrated that margetuximab plus chemotherapy had an increasing cost of 68,132 and 20,540 over trastuzumab plus chemotherapy in the US and China, respectively, with a gain of 0.11 and 0.09 QALYs both favored margetuximab. The ICERs for two treatment strategies were 260,176 in the US and 630,777 in China, resulting in a poor cost-effectiveness at their respective threshold of willingness to play. One-way sensitivity analyses showed that the results to be most sensitive to the price of margetuximab and that of trastuzumab. And a 11% and 82% price reduction of margetuximab would make this regimen cost-effective in the US and China, respectively. Conclusion: In the US and China, margetuximab plus chemotherapy is not likely to be cost-effective for women with pretreated ERBB2-positive advanced breast cancer, whereas price reduction effectively improves insufficient cost-effectiveness.